2018
DOI: 10.1007/s00181-018-1448-1
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous effects in the international transmission of the US monetary policy: a factor-augmented VAR perspective

Abstract: This paper analyses the international transmission of US monetary policy shocks. We use a time-varying, factor-augmented VAR framework to examine how and to what extent the propagation of US policy shocks affects the South East Asian (SEA) and European Union (EU) economies, through various transmission channels. We find that in the SEA economies, the income absorption effect is the most pronounced channel as indicated by the significant worsening of the trade balance of these countries, which provokes a reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…More specifically, I extract the first principal component of cross-country asset prices of four asset types, overnight rates, 3-year bond yields, equity prices, and FX rates visà-vis the U.S. dollar. 54 In this way, the asset prices in open economies are represented as a FAVAR framework (as in Evgenidis et al, 2019;Spiegel & Tai, 2017), where domestic asset prices are represented by three types of variables (U.S., domestic, and world financial asset prices in the rest of the world). 55 The estimation results are reported in Figure A8.…”
Section: Alternative Measure Of Global Variables (Principal Component Analysis)mentioning
confidence: 99%
“…More specifically, I extract the first principal component of cross-country asset prices of four asset types, overnight rates, 3-year bond yields, equity prices, and FX rates visà-vis the U.S. dollar. 54 In this way, the asset prices in open economies are represented as a FAVAR framework (as in Evgenidis et al, 2019;Spiegel & Tai, 2017), where domestic asset prices are represented by three types of variables (U.S., domestic, and world financial asset prices in the rest of the world). 55 The estimation results are reported in Figure A8.…”
Section: Alternative Measure Of Global Variables (Principal Component Analysis)mentioning
confidence: 99%
“…For example, Gómez-Zaldívar et al (2013) studied three explanatory stimuli and found that the exchange rate oscillations describe a key portion of the deviations in equity index returns for developed countries. Evgenidis et al (2019) empirically studied returns of 18 developed markets using multifactor asset pricing models. Factors selected for this study were global economic risks and it concluded that foreign exchange risk was the most decisive factor in defining international equity index returns.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Mohanty (2014) notes that central bank practitioners identify the adjustment in the exchange rate and the monetary policy rate as the prime channels of monetary policy transmission from advanced to emerging economies: the former is singled out as the main channel in economies with a floating exchange rate regime, the latter with a fixed exchange rate regime. Rey (2016) and Evgenidis et al (2019) point out that in a floating exchange rate regime, monetary policy impulses can exert influence on the trade balance of domestic and foreign economies in two opposing ways: demand-augmenting effects and expenditure-switching effects. A contractionary domestic monetary policy impulse weakens domestic demand including imports, which improves the domestic trade balance (demand-augmenting effect) and, at the same time, an increase in domestic policy rate may induce a real appreciation of the domestic currency, which in turn worsens the domestic trade balance (expenditure-switching effect) and affects other domestic and foreign macroeconomic variables (ibidem).…”
Section: Literature Reviewmentioning
confidence: 99%